Analysis of Profitability Ratios in Assessing the Profitability of PT GoTo Gojek Tokopedia Tbk for the 2023–2024 Period - Mohammad Nabilulhaq D; Luthviyah Ismayati; Satrio Sulistiyanto; Gustiara Chairunisa; Asri Sundari (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the use of profitability ratios in evaluating PT GoTo Gojek Tokopedia Tbk’s ability to generate profits following the business restructuring and deconsolidation of Tokopedia during the 2023–2024 period. Research Method: This study employs a descriptive quantitative approach through the analysis of financial statements. Secondary data were obtained from PT GoTo’s audited financial statements, annual reports, sustainability reports, and public exposés for the 2023–2024 period. The analysis was conducted using Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). Results and Discussion: Revenue increased, but gross profit margin (GPM) declined due to a rise in cost of revenue. In contrast, net profit margin (NPM), return on assets (ROA), and return on equity (ROE) improved compared to the previous year, in line with a reduction in net loss and greater efficiency in operating expenses. Nevertheless, all net income-based ratios remain negative, indicating that the company has not yet achieved positive profitability. Implications: An evaluation of a digital company’s profitability must take into account business restructuring, operational efficiency, and the impact of accounting factors in addition to changes in ratio values. Originality: This study offers a contextual interpretation of profitability ratios in post-deconsolidation digital companies by integrating financial ratio analysis with changes in business structure.